Monitoring heritage buildings with wireless sensor networks: The Torre Aquila deployment - Ceriotti, Matteo; Mottola, Luca; Picco, Gian Pietro; Murphy, Amy L.; Guna, Stefan; Corra, Michele; Pozzi, Matteo; Zonta, Daniele; Zanon, Paolo (2009 International Conference on Information Processing in Sensor Networks, 2009)
Wireless sensor networks are untethered infrastructures that are easy to deploy and have limited visual impact—a key asset in monitoring heritage buildings of artistic interest. This paper describes one such system deployed in Torre Aquila, a medieval tower in Trento (Italy). Our contributions range from the hardware to the graphical front-end. Customized hardware deals efficiently with high-volume vibration data, and specially-designed sensors acquire the building's deformation. Dedicated software services provide: i) data collection, to efficiently reconcile the diverse data rates and reliability needs of heterogeneous sensors; ii) data dissemination, to spread configuration changes and enable remote tasking; iii) time synchronization, with low memory demands. Unlike most deployments, built directly on the operating system, our entire software layer sits atop our TeenyLIME middleware. Based on 4 months of operation, we show that our system is an effective tool for assessing the tower's stability, as it delivers data reliably (with loss ratios ≪0.01%) and has an estimated lifetime beyond one year.